Root resorption in endodontically treated teeth that have been subjected to orthodontic forces - Pimenta, Roberto César Bossi; de Oliveira, Warley Silva; Teodoro, Maria Cláudia Nunes Araújo; Pereira , Renata Afonso da Silva; Paiva, Juliana de Carvalho Carmelo; Figueira, Luciano Henrique; Georjutti, Renata Pereira; Teruel, Eduardo Zanzin; Neto, Akel Fares Akel; Souto-Souza, Debora (Seven Editora, 2024)
Root resorption, also known as external apical resorption or induced apical resorption, expressed as apical rounding, is one of the most recurrent findings in orthodontic practice. This pathology, when it occurs due to orthodontic movement, is a consequence of the mechanical and physiological reactions that occur at the cellular level. These reactions are part of the apical remodeling process, and are therefore inevitable in most cases, and acceptable in orthodontic practice. The search for orthodontic treatment by adult patients is growing more and more, which leads to an increase in the number of pulped teeth subjected to orthodontic forces. In view of this fact, studies comparing the consequences of these mechanotherapies in pulped teeth in relation to vital teeth in the context of root resorption are pertinent. This study aims to evaluate root resorptions induced by orthodontic movements in teeth previously treated endodontically. Research on root resorption comparing vital teeth and pulped teeth uses animal studies, radiographic analyses, histological studies and clinical cases. Studies have shown that it cannot be confirmed that endodontically treated teeth have greater resorption, showing that they move just like vital teeth when submitted to orthodontic treatment and that root resorption is a multifactorial phenomenon. Therefore, it is recommended to wait for the success of the endodontic treatment to be proven, as well as the elimination of all inflammatory exudate, so that orthodontic treatment can begin. DOI:https://doi.org/10.56238/sevened2024.016-018